Perceived benefits as a driver and necessary condition for the willingness of air passengers to provide personal data for non-mandatory digital services at airports - Mwesiumo, Deodat; Halpern, Nigel; Bråthen, Svein; Budd, Thomas; Suau-Sanchez, Pere (Elsevier, 2023)
The willingness of individuals to provide personal data is of interest to policymakers and practitioners seeking to develop more intelligent transportation systems that create value for passengers using technologies, as well as to leverage the use of data more generally to accelerate digital transformation. This study examines the role of perceived benefits as a driver and necessary condition for the willingness of air passengers to provide personal data for non-mandatory digital services at airports. These are services that are not essential for the operation of the airport or for the safety and security of passengers but can enhance the passenger experience or generate additional revenue for the airport. Examples include receiving notifications to a mobile device about their journey and related products and services, accessing customer services online, joining and receiving electronic information from an airport loyalty programme, and making payments for products and services online or via a mobile application. The analysis is based on two samples of 235 and 218 respondents to an online survey where the second sample is used for the purpose of replication. Responses were analysed using a recently developed complementary approach that combines partial least squares structural equation modeling and necessary condition analysis. The findings confirm that perceived benefits are a significant driver and necessary condition for passengers’ willingness to provide personal data. More so, perceived benefits significantly attenuate the negative effect that privacy concerns have on passengers’ willingness to provide personal data. The findings offer theoretical and methodological contributions, as well as implications for policy and practice.
Keywords: Digital services at airports; Perceived benefits; Privacy concerns; Privacy calculus; Willingness to provide personal data